Management and Utilization of Nusa Penida Island by Foreign Nationals in Relation to Licensing Regulations in Indonesia - Fidya Ramadhani; Liza Priandhini (Faculty of Law, Universitas Pekalongan, 2024)
This paper examines the management andutilization of small islands in Indonesia,specifically Nusa Penida, by foreign nationals(WNA) in relation to the prevailing legalregulations on land and investment permits.Indonesia, being an archipelagic nation, ishome to numerous islands that attract bothlocal and foreign investors, especially intourism. The legal framework governingforeign investment in small islands, includingthe necessary permits, is explored, withparticular focus on the requirements set out inthe Indonesian legal system, such as the UUPA(Agrarian Law), the Management of CoastalAreas and Small Islands (PWP3K Law), andvarious ministerial regulations.The paper addresses how foreign nationalsengage in island management in Nusa Penida,particularly in tourism-related ventures likehotels, resorts, and recreational activities suchas diving and snorkeling. It evaluates theimpact of such foreign investments on the localcommunity, highlighting both positive andnegative aspects. One significant issuediscussed is the long-term land leasingagreements between foreign nationals andIndonesian landowners, which may potentiallylead to unintended ownership transfers andlegal disputes, as well as challenges in ensuringcompliance with Indonesian land laws.The study also delves into the regulatory gapsin the implementation of these laws,particularly the lack of clear proceduralguidelines for foreign investment in smallislands. Furthermore, it calls for stricterenforcement and monitoring of land use andproperty transactions to prevent theunregulated acquisition of land by foreignnationals and to protect the national interest.Finally, the paper offers recommendations forimproving legal oversight, such as ensuringproper registration of land transactions,enhancing the role of notaries and land officialsin verifying the legality of land agreements,and ensuring that foreign investments arealigned with Indonesia's economic andenvironmental goals. The findings suggest thatwhile foreign involvement in small islandmanagement can contribute to the localeconomy, stringent legal frameworks andthorough monitoring are essential to safeguardthe nation's sovereignty over its naturalresources.